Child outcomes after induction of labour or expectant management in women with preterm prelabour rupture of membranes between 34 and 37 weeks of gestation: study protocol of the PPROMEXIL Follow-up trial. A long-term follow-up study of the randomised controlled trials PPROMEXIL and PPROMEXIL-2. Issue 6 (15th June 2021) - de Ruigh, Annemijn A; Simons, Noor E; Van 't Hooft, Janneke; van Wassenaer-Leemhuis, Aleid G; Aarnoudse-Moens, Cornelieke S H; van Wely, Madelon; van Baaren, Gert-Jan; Vlemmix, Floortje; van der Ham, D P; van Teeffelen, Augustinus S P; Mol, Ben W; Roseboom, Tessa J; et al.
Abstract : Introduction: Late preterm prelabour rupture of membranes (PROM between 34 +0 and 36 +6 weeks gestational age) is an important clinical dilemma. Previously, two large Dutch randomised controlled trials (RCTs) compared induction of labour (IoL) to expectant management (EM). Both trials showed that early delivery does not reduce the risk of neonatal sepsis as compared with EM, although prematurity-related risks might increase. An extensive, structured long-term follow-up of these children has never been performed. Methods and analysis: The PPROMEXIL Follow-up trial (NL6623 (NTR6953)) aims to assess long-term childhood outcomes of the PPROMEXIL (ISRCTN29313500 ) and PPROMEXIL-2 trial (ISRCTN05689407 ), two multicentre RCTs using the same protocol, conducted between 2007 and 2010 evaluating IoL versus EM in women with late preterm PROM. The PPROMEXIL Follow-up will analyse children of mothers with a singleton pregnancy (PPROMEXIL trial n=520, PPROMEXIL-2 trial n=191, total IoL n=359; total EM n=352). At 10–12 years of age all surviving children will be invited for a neurodevelopmental assessment using the Wechsler Intelligence Scale for Children-V, Color-Word Interference Test and the Movement Assessment Battery for Children-2. Parents will be asked to fill out questionnaires assessing behaviour, motor function, sensory processing, respiratory problems, general health and need for healthcare services. Teachers will fill out the Teacher Report Form and answer questions regarding school attainment. For all tests means with SDs will be compared, as well as predefined cut-off scores for abnormal outcome. Sensitivity analyses consisting of different imputation techniques will be used to deal with lost to follow-up. Ethics and dissemination: The study has been granted approval by the Medical Centre Amsterdam (MEC) of the AmsterdamUMC (MEC2016_217). Results will be disseminated through peer-reviewed journals and summaries shared with stakeholders. This protocol is published before analysis of the results. Trial registration number: NL6623 (NTR6953).